PENGARUH GIBBERELLIC ACID (GA3) TERHADAP KACANG TANAH (Arachis hypogea L) PADA FASE GENERATIF - Yennita, Yennita (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - This study aimed to examine the effect of GA3 to peanuts on the generative phase. Using a completely randomized design(CRD) with five treatment sand five replications, treatments were:0 ppm GA3, 20 ppm, 40 ppm 60 ppm and 80 ppm GA3. GA3. The observations made are: when the first flowers appear, the numberof flowers, number of fruits, fruit weight planting. The data were analyzed by ANOVA 1 factor, if F major hit f Table continued with DNMRT test at level 5%. From the results showed that administration of GA3 significantly affect the number of flowers and number of pods, but did not significantly affect the time the first flowers appear and the weight of planting pods. It can be concluded that the administration of GA3 increase the numberof flowers and number of pods on the plant peanutsÂ Keywords: gibberellic acid(GA3), peanuts (Arachis hypogea. L)